Analysis on Flow Induced Motion of Cylinders with Different Cross Sections and the Potential Capacity of Energy Transference from the Flow - Jijian Lian; Xiang Yan; Fang Liu; Jun Zhang (Shock and Vibration)
The energy in flow induced motion (FIM) was harnessed in recent years. In this study, the energy transfer ratio was derived to estimate the energy transference from the flow to the FIM. Then the FIM characteristics and energy transference of cylinders with different cross sections were experimentally investigated. The main findings are listed as follows. (a) Circular cylinders and diamond prisms both present a self-limited motion. The maximum amplitude ratio of circular cylinder is around 1~1.2 which is higher than that of diamond prism (0.4~0.5). (b) Triangle prisms and right square prisms present a self-unlimited motion. For triangle prism, amplitude ratio increases over 1.8; for right square prisms, amplitude ratio reaches 1.2. (c) The maximum transfer ratios of circular cylinder and triangle prism are 80% and 57%, respectively, which are much higher than those of other prisms, indicating that circular cylinder and triangle prism have better performances in energy transference. (d) The transfer ratio is strongly dependent on the damping and mass; higher damping or mass will promote a higher transfer ratio. (e) Beyond the critical transfer ratios, amplitude variation coefficients are around 10%~30% resulting in a better performance in stationarity.